KINERJA PENYULUH PERTANIAN DI DESA KAPU JAYA KECAMATAN PALANGGA KABUPATEN KONAWE SELATAN - Riska Riska; Hartina Batoa; Salahuddin Salahuddin (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2026)
The agricultural sector plays a pivotal role in the economy and the general welfare of the population. The success of agricultural endeavors, as evidenced by the increased corn production in Kapu Jaya Village, is contingent upon the efficacy of agricultural extension workers. These extension workers are responsible for modifying behaviors, enhancing farmers' knowledge, and facilitating the overcoming of various production constraints. The objective of this study is to assess the effectiveness of agricultural extension workers in Kapu Jaya Village, Palangga District, South Konawe Regency. The research population consists of all 97 corn farmers in Kapu Jaya Village, resulting in a sample size of 25 people. The sampling method employed was a simple random sampling technique. The data presented herein was collected through a variety of research methods, including surveys, interviews, and documentation. The research variable was the performance of agricultural extension workers. The collected data was then subjected to both descriptive and quantitative analysis. The results indicated that the performance of agricultural extension workers in Kapu Jaya Village was high in terms of preparation, implementation, and evaluation. The extension workers demonstrated proficiency in planning, implementing extension services tailored to the needs of farmers, conducting regular evaluations, and submitting reports. This high performance is indicative of the capacity of extension workers to enhance farmers' capabilities, fortify institutions, and promote augmented agricultural productivity. A structured planning approach, the implementation of adaptive extension methods, and the continuous evaluation of program effectiveness are essential for ensuring the success of agricultural extension programs at the village level.